Roadsign detection and recognition (RSDR) - Lim, Chin Huey (2010)
Road-sign Detection and Recognition via Video (RSDR) is a system that able to detect and recognize a road-sign on a motion video. This is due to the rapid changes of the technologies, more and more technologies recognize are able to provide high performance for people to carry their daily task. In RSDR, it is a system help the driver to recognize the shape of road-sign while the driving task is carried. Before this, most of the processing in digital image is based on still image. The limitation on still images is unable to perform effectively then motion video. Motion video can be processed directly in real-time by capturing the data to be examine, while for the still image the captured data is not in real-time thus the information cannot be delivered in short time. This RSDR will be developed according to methodology of waterfall models and it weakness is overcome by applied the incremental and iterative development process. Because with the well defined of the requirement on RSDR, the waterfall model is chooses to produce a high quality system. In case, there is some of the uncountable event occur required changes on development process the support of incremental and iterative development process can be help to overcome this problem arise. The method of template matching is used to recognize the road-sign. Before the recognition process, the detection of the road-sign on motion video is being done in Matlab by applied the Video and Image Processing techniques control by simulation process to detect an object from motion video. Only the successful of the object extracted from video frame will proceed to template matching on recognition process based on the template in the database. In conclusion, RSDR is potentially being a smart system in future for user to gather information from real-time process such as the driving task.